Стратегія і тактика охорони рідкісних і зникаючих видів у ботанічних садах - Melnik, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
Modern state of the rare and threatened species protection in Ukraine and abroad are considered. Main problems and ways of its improvement are outlined. Modeling of the populations in the Forest-Steppe cultural phytocoenoses and plantations by the type of geographical cultures are more perspective methods of protection of the rare and threatened species ex situ.